Cognitive approaches to L3 acquisition - Garcia Mayo, Maria del Pilar (International Journal of English Studies, 2012)
Multilingualism has established itself as an area of systematic research in linguistic studies over the last two decades. The multilingual phenomenon can be approached from different perspectives: educational, formal linguistic, neurolinguistic, psycholinguistic and sociolinguistic, among others. This article presents an overview of cognitive (psychological and formal linguistic) approaches to third language (L3) acquisition where the assumption is that language acquisition is a complex multi-faceted process. After identifying what is meant by L3, the article briefly reviews the major issues addressed from both the psycholinguistic strand and the emerging L3 linguistic strand and concentrates on those aspects that are in need of further research in both.